0=3x+9

Simple and best practice solution for 0=3x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0=3x+9 equation:


Simplifying
0 = 3x + 9

Reorder the terms:
0 = 9 + 3x

Solving
0 = 9 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
0 + -3x = 9 + 3x + -3x
Remove the zero:
-3x = 9 + 3x + -3x

Combine like terms: 3x + -3x = 0
-3x = 9 + 0
-3x = 9

Divide each side by '-3'.
x = -3

Simplifying
x = -3

See similar equations:

| 8c-3(c+4)=43 | | (x-6)/14=(7x)/21 | | 5x-18=2x+30 | | 2x^2+3y^2=30 | | 7+18/(6-3) | | 4(t-6)+8t=6(2t+4)-12 | | 5x^2+30x+150=1220 | | 5x+15=220000 | | -30=5+5u | | (3x/7)+3=24 | | x/6+8=26 | | -1/3m-4=22 | | 3m+15+2m-15=7m+15 | | 360*67/72*11/25 | | 2(2-4x-9x)+6(5x+2)=28 | | 5z-18z= | | 3(x-3)-5=16 | | 4x+5=5x+5 | | 0.04x+4=40 | | 4x-3=4x-3 | | 4(-8x+5)= | | y+4= | | 6(c+4)=4-18 | | 4(x-3)=4x-12 | | (4x+10)+3x=185 | | 4x-3=12x-3 | | x+x+x^2=182 | | 4(x+3)=4(x+15) | | 241=20-w | | 7x+7=33+29x | | 6(x-8)=6x+48 | | 5d=9+2d |

Equations solver categories